Modeling and simulation of discrete-event systems - Choi, Byoung Kyu, 1949- (John Wiley & Sons Inc., 2013)
Computer modeling and simulation (M & S) allows engineers to study and analyze complex systems. Discrete-event system (DES)-M & S is used in modern management, industrial engineering, computer science, and the military. As computer speeds and memory capacity increase, so DES-M & S tools become more powerful and more widely used in solving real-life problems./ Based on over 20 years of evolution within a classroom environment, as well as on decades-long experience in developing simulation-based solutions for high-tech industries, iModeling and Simulation of Discrete-Event Systems /iis the only book on DES-M & S in which all the major DES modeling formalisms ' activity-based, process-oriented, state-based, and event-based ' are covered in a unified manner:/ ulliA well-defined procedure for building a formal model in the form of event graph, ACD, or state graph/liliDiverse types of modeling templates and examples that can be used as building blocks for a complex, real-life model/liliA systematic, easy-to-follow procedure combined with sample C♯ codes for developing simulators in various modeling formalisms/liliSimple tutorials as well as sample model files for using popular off-the-shelf simulators such as SIGMA, ACE, and Arena/liliUp-to-date research results as well as research issues and directions in DES-M & S/li/ul iModeling and Simulation of Discrete-Event Systems /iis an ideal textbook for undergraduate and graduate students of simulation/industrial engineering and computer science, as well as for simulation practitioners and researchers.- Resumé vydavatel
Includes index.
Keywords: diskrétní dynamické systémy; modelování a simulace; discrete dynamical systems; modeling and simulation; elektronické knihy; učebnice; electronic books; textbooks